2011
DOI: 10.1155/2011/345048
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Ridge Preservation Using Leukocyte and Platelet-Rich Fibrin: A Report of a Case

Abstract: In order for a dental implant to be restored optimally, it must be placed in an ideal anatomic position. However, this is not always possible, since physiological wound healing after tooth removal, often results in hard and soft tissue changes which ultimately compromises ideal implant placement. With the aim of minimising the need for tissue augmentation, several alveolar ridge preservation (ARP) techniques have been developed. These often require the use of grafting material and therefore increase the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…The suitability of PRF as a biologically active scaffold has been illustrated in a number of studies revealing proliferation and differentiation of osteoblasts and gingival fibroblasts [8, 9]. Clinical studies have demonstrated that PRF promotes soft tissue and bone regeneration [10, 11], as well as periodontal tissue regeneration [12, 13]. The ability of PRF to augment and regenerate compromised tissues may be enhanced in combination with bone substitutes such as Bio-Oss or autologous bone [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of PRF as a biologically active scaffold has been illustrated in a number of studies revealing proliferation and differentiation of osteoblasts and gingival fibroblasts [8, 9]. Clinical studies have demonstrated that PRF promotes soft tissue and bone regeneration [10, 11], as well as periodontal tissue regeneration [12, 13]. The ability of PRF to augment and regenerate compromised tissues may be enhanced in combination with bone substitutes such as Bio-Oss or autologous bone [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…The biomaterial acts by releasing high-concentration growth factors to the wound site, thereby stimulating healing and new bone formation [17]. Unlike other socket preservation procedures, the use of PRF is a simple method that requires minimal cost and reduces the need for grafting material.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs études cliniques ont été menées afin de détermi-ner son potentiel clinique : -Peck et al proposent l'utilisation du PRF seul pour préserver la hauteur et l'épaisseur de l'os alvéolaire après une extraction [4]. Une partie de la membrane de PRF est découpée en plusieurs morceaux qui sont déposés dans l'alvéole, tandis que l'autre partie est posée contre l'os alvéolaire et recouverte par le lambeau muco-gingival.…”
Section: Discussionunclassified